(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In this paper, we analyzed the data of the 17 body sizing measurement parameters of 300 adult male participants who were Shaanxi adult male aged 20 ∼ 50, which were collected by using the 3D automatic measurement, 3D interactive measurement and manual measurement. We compared the data of the 3D automatic measurement with those of the 3D interactive measurement and the manual measurement. From the results of the analysis, we can draw the following conclusions: (1) Deviation between the manual measurement and the 3D scanning measurement existed obviously, which cannot be ignored; (2) In the 3D automatic measurement, as the result of the deviation of the identification to the bone location, the measurement data must be checked and modified interactively; (3) The posture of the participant has a significant efect on the measurement data, and the specified basic stance will affect the measurements of shoulder, breast and waist. Therefore, the scanning posture should be standardized based on the need of the study. For example the stance with feet together can make the height measurement more accurate; (4) Many factors would interfere with the accuracy of the manual measure and result the difference with 3D measurement, such as the breathing and posture of the participants, and the measurement skill, experience, position mark etc. (5) There is a linear relation between the manual measurement and the 3D scanning measurement. By establishing the linear regression model the measurement data can be forecasted and calculated.